Knowledge and practices of healthcare workers in prevention and control of hospital-acquired infections in the Maternity Department at Bindura Provincial Hospital, Zimbabwe - Chpfuwa, Tirivanhu; Mwanza, Estele; Tirivavi, Elizabeth; Chigonde, Chipo (International Journal of Infection Control, 2023)
Infections acquired in hospitals are the most frequent negative consequences of the healthcare delivery system, which affects both developed and developing nations. Among hospitalized patients and healthcare professionals, they are among the top causes of mortality and morbidity. Therefore, healthcare professionals are crucial in preventing and controlling hospital-acquired illnesses and safeguarding patients. The purpose of this study was to determine the knowledge and practices of healthcare workers (HCWs) in the prevention and control of hospital-acquired infections (HAIs) in the Maternity Department at Bindura Provincial Hospital. A cross-sectional study design was used to collect data from 46 participants using a self-administered questionnaire. Of which, 54.3% had 2 to 5 years of experience. With regard to the knowledge of HAIs, 59% of HCWs did not know what HAIs were, 57% did not know that cleaners and mothers should be engaged in infection prevention and control (IPC) activities, whereas 85% did not know that ventilator-associated infections and COVID-19 (57%) are HAIs. Segregation of waste was shown to be poorly practiced with 56% of HCWs, 65% were unaware of the hospital’s IPC policy, and 7% had never utilize the manuals of standard operating procedures when performing their jobs. This study recommended that every HCW should receive instruction on IPC methods from the facilities’ IPC coordinators, who should also regularly supervise the staff to monitor compliance with IPC. Mothers should receive more education on the prevention of infections when first admitted to the ward.